KINERJA DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU DALAM PELAKSANAAN FUNGSI LEGISLASI TAHUN 2014 - ", Ranggi; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research present describe the performances of legislator of Riau Province in create a legislation function. In order that describe the some factors that influence of performance of legislator of Riau Province in create a legislation function. Legislations are one of most function of legislators. In 2014 Legislators of Riau Province create a twelve a district regulations and eight of district regulations that has a rativications.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Riau Province and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan research likes Head of Legislator Riau Province, Head of Legislative organ in Riau Province and Secreaty of Legislative Riau Province.The conclusion of this research are performance of legislator of Riau Province in create a legislation function are has done with some mechanism likes planning, organizing, discussion and rativication of district regulation. Some of factors that cause are skill and comptence of legislator, coordination between ecsecutive and legislative and implementations of regulatons.Keywords:performanc, legislative and legislation.